Treatment of ADHD in Neurofibromatosis Type 1 - J Gordon Millichap (Pediatric Neurology Briefs)
The cognitive and behavioral problems and effects of treatment of attention deficit hyperactivity disorder (ADHD) in 20 children with NF1 and ADHD were compared to 26 control children with NF1, 14 controls with ADHD, and 14 controls with normal development, studied at Klinikum Nord Ochsenzoll. Hamburg, Germany.